Hubungan antara persepsi maloklusi dengan psikososial remaja di SMA Negeri 1 Denpasar, Bali-Indonesia - Ni Putu Putri Wulandari; Louise Cinthia Hutomo; Naomi Vembriati (School of Dentistry Faculty of Medicine Udayana University, 2020)
Background: Physical apperance, especially dental appearance is an important thing for adolescent for the process of identity establishment. Dental apperance contributes to the assessment of facial appearance, as a determinant attractiveness of physical appearance and social interaction. One of the factors that contribute to dental appearance is malocclusion. Perception of malocclusion can affect on adolescent self-esteem, psychological condition even social relationship. The aim of the study is to determine the relationship between perception of malocclusion with adolescent psychosocial in SMA Negeri 1 Denpasar. Method: crossectional analytic design was used in this study. The samples of this study was 217 students and selected by stratified random sampling. The perception of malocclusion measured using Aesthetic Component of Index Othodontic Treatment Need (IOTN) and adolescent psychosocial was measured using Pychosocial Impact of Dental Aesthetic Questionnaire (PIDAQ). Spearman Rank Correlation was used to test the hypothesis.Result: there is significant correlation between perception of malocclusion with adolescent psychosocial in SMA Negeri 1 Denpasar (p=0.000) with coefficient correlation is 0,401. Conclusion: there is correlation between perception of malocclusion with adolescent psychosocial in SMA Negeri 1 Denpasar. Latar belakang: penampilan fisik terutama penampilan dental merupakan hal yang penting bagi remaja dalam proses pembentukan identitas diri. Penampilan dental berkontribusi terhadap penilaian penampilan wajah, sebagai penentu menarik atau tidaknya penampilan fisik serta berperan terhadap interaksi sosial. Salah satu faktor yang berperan terhadap penampilan dental adalah maloklusi. Persepsi terhadap maloklusi dapat berdampak pada harga diri remaja maupun kondisi psikologis serta hubungan sosialnya. Penelitian ini bertujuan untuk mengetahui hubungan antara persepsi maloklusi dengan psikososial remaja di SMA Negeri 1 Denpasar.Metode: desain penelitian ini adalah analitik cross sectional. Sampel penelitian ini berjumlah 217 siswa dan dipilih dengan metode stratified random sampling. Persepsi maloklusi diukur dengan Aesthetic Component dari Index Orthodontic Treatment Need (IOTN) dan psikososial remaja diukur dengan Pychosocial Impact of Dental Aesthetic Quistionnaire (PIDAQ). Uji hipotesis menggunakan uji korelasi Spearman Rank.Hasil : terdapat hubungan yang signifikan antara persepsi maloklusi dengan psikososial remaja di SMA Negeri 1 Denpasar (p=0,000) dengan koefisien korelasi sebesar 0,401. Simpulan: terdapat hubungan antara persepsi maloklusi dengan psikososial remaja di SMA Negeri 1 Denpasar.